Effects of elastic foundation and the Poisson’s ratio on the nonlinear buckling and postbuckling behaviors of imperfect FGM plates subjected to mechanical loads - Pham, Hong Cong (H. : ĐHQGHN, 2017)
This paper presents an analytical approach to investigate effects of elastic foundation and the Poisson’s ratio on the nonlinear buckling behavior of imperfect FGM plates, subjected to mechanical loads. Material properties are assumed to be temperature independent, and graded in the thickness direction according to a power law distribution in terms of volume fractions of constituents. Equilibrium and compatibility equations are derived by using classical plate theory taking into account geometrical nonlinearity, initial geometrical imperfection and elastic foundation with Pasternak model. Galerkin method is used to determine explicit expressions of buckling loads and postbuckling paths. Analysis is carried out to assess the effects of material, geometrical, elastic foundation parameters on the stability of FGM plates.